COVID-19 : the great reset - Schwab, Klaus, 1938-; Malleret, Thierry, 1961- (Cologne/Genève, Suisse : World Economic Forum, 2020)
"This book provides a worrying yet hopeful analysis. COVID-19, as the greatest public health crisis of the century has led to enormous economic devastation and made existing inequities worse. But the power of human beings lies in their foresight, ingenuity and - at least to a certain extent - ability to take their destiny into their hands and plan for a better future. This book shows us where to start."--Publisher's statement.
1. Macro reset: 1.1. Conceptual framework -- three defining characteristics of today's world ; 1.2. Economic reset ; 1.3. Societal reset ; 1.4. Geopolitical reset ; 1.5. Environmental reset ; 1.6. Technological reset -- 2. Micro reset (industry and business): 2.1 Micro trends ; 2.2. Industry reset -- 3. Individual reset: 3.1. Redefining our humanness ; 3.2. Mental health and well-being ; 3.3. Changing priorities.
Includes bibliographical references.
Keywords: COVID-19 (Disease); COVID-19 (Disease) -- Economic aspects; COVID-19 (Disease) -- Social aspects; COVID-19 (Disease) -- Political aspects; COVID-19 (Disease) -- Environmental aspects; COVID-19 (Disease) -- Psychological aspects; COVID-19; COVID-19.; COVID-19 -- Aspect de l'environnement.; COVID-19 -- Aspect psychologique; COVID-19 -- Aspect social; COVID-19; COVID-19 -- Aspect politique; COVID-19 (Disease) -- Psychological aspects; COVID-19 (Disease) -- Political aspects; COVID-19 (Disease) -- Environmental aspects; COVID-19 (Disease) -- Economic aspects; COVID-19 (Disease); COVID-19 (Disease) -- Social aspects